Membangun Sustainability Awareness Siswa: Peran Literasi Sains Matematis, Lingkungan, dan Sikap Kewarganegaraan - Elice Twenty Saragih; Monica Kristin Siburian; Marlina G. Munthe; Katarina Lestari Simbolon; Diva Syania Lubis; Hisar Marulitua Manurung (Yayasan Bayt Shufiya Nusantara, 2025)
Educational institutions are now required to prepare a generation equipped with strong sustainability awareness. This study aims to examine how scientific–mathematical literacy, environmental literacy, and citizenship literacy can be conceptually integrated to build a holistic form of sustainability awareness among students. Employing a library research method, this study reviews a wide range of scholarly sources, including journal articles, academic books, policy reports, reputable websites, news media, and current magazines. The analysis focuses on several stages: conceptual categorization, thematic synthesis, theoretical comparison, and a critical appraisal of relevant empirical findings. The study reveals that scientific–mathematical literacy plays an essential role in enabling students to interpret environmental issues as scientific and data-driven problems; environmental literacy cultivates ecological empathy and systemic ecological thinking; and citizenship literacy expands students’ environmental understanding into public action and civic responsibility. Together, these literacies complement one another and serve as a foundational triad for developing sustainability awareness across cognitive, affective, and practical dimensions. The study concludes that sustainable education strengthening curriculum and pedagogy is therefore crucial to ensure that schools become formative spaces for nurturing a responsible and sustainability-minded generation for the future of development.